Paisagem linguística urbana na fronteira: dinâmicas e identidades sociais - Lecheta, Michelle (2020)
The current research proposes to set the eye on the public spaces of Foz do Iguaçu city, located in the Triple Border region (BR-PY-AR), which are appropriated by minoritarian groups who print their identities and demands in form of phrases and linguistic symbols on walls – what is here called ‘linguistic manifestation’. From the concepts of Linguistic Landscape (LANDRY; BOURHIS, 1997; SHOHAMY, 2006; SPOLSKY, 2009) this research seeks, at first, the comprehension of the way the linguistic landscape of the public urban space of Foz do Iguaçu is featured in relation to those linguistic manifestations. Considering the exhibition of photographs taken from the manifestations located in the central area of the city and the analyses of questionnaires that were applied to the exhibition viewers, it is also intended to understand what the perception of the urban walkers who transit on the spaces where there are linguistic manifestations is. It is generally intended, therefore, the comprehension of how this perception might contribute to the visibility of the groups which are represented on the walls, legitimizing or not their demands, being able to trigger on the passing-by receptors the development of a critical reading of the urban landscape and of the social issues which are imbricated in it. This study has, therefore, an interdisciplinary approach (LEIS, 2011), visual data collect (FLICK, 2008) and qualitative data processing, including discussion based on the power relations (FOUCAULT, 1979; 1995; 2010; 2014), in order to emphasize the resistance feature of these manifestations since they make themselves present on space where the cleanness is “normatized”. It also includes analytic elements from the Geography of Visibility (GOMES, 2013), in order to subsidize the comprehension of the urban landscape perception where the analyzed manifestations are inserted. As a result, the data analysis has suggested that the urban passersby are aware of the linguistic manifestations which compose the city landscape and that the observation of the content expressed on these manifestations may mobilize different perceptions on these passersby, revealing the way they relate to the city through this social-linguistic phenomenon.